Peran Positive Emotion dalam Memediasi Pengaruh Hedonic Shopping Value Terhadap Impulse Buying (Studi Kasus: Mall Bali Galeria) - Naentiana, Putu Vera; Setiawan, Putu Yudi (E-Jurnal Manajemen; Vol 3 No 8 (2014), 2014)
This study aims to determine the effect of hedonic shopping value, positive emotion towards impulse buying, the influence of hedonic shopping value to positive emotion, positive emotion and the role of mediation in the hedonic shopping value against impulse buying at Mall Bali Galeria. This research was conducted in Badung , samples taken 130 respondents with purposive sampling method. Data were collected by questionnaires using a 5-point Likert scale, to measure 13 indicators. The analysis technique used Structural Equation Modeling (SEM). These results indicate that hedonic shopping value , give the positive emotion and significant effect on impulse buying, hedonic shopping value positive and significant effect on positive emotion, positive emotion as well as a significant effect in mediating hedonic shopping value against impulse buying. This shows that the variable hedonic shopping value, and positive emotion effect impulse buying.
Keywords: Peran Positive Emotion dalam Memediasi Pengaruh Hedonic Shopping Value terhadap Impulse Buying (Studi Kasus: Mall Bali Galeria)